Smart antennas in wireless communications base-station diversity and handset beamforming. - Dietrich, Carl B. Jr.
We review diversity and smart antenna research applied to both base-stations and terminals. To illustrate the performance gains possible, the paper describes research being conducted by the Smart Antenna Group at Virginia Tech, in both smart base-stations and smart handheld terminals.
Keywords: Land mobile radio cellular systems; Land mobile radio equipment; Land mobile radio diversity systems; Array signal processing; Land mobile radio cellular handsets; Smart antennas